MAMMARY ANALOGUE SECRETORY CARCINOMA: AN EVALUATION OF ITS GENETIC AND CLINICAL CHARACTERISTICS. (February 2015) - Luk, Peter P.; Selinger, Christina; Eviston, Tim; Lum, Trina; O'Toole, Sandra A.; Clark, Jonathan R.; Gupta, Ruta
Abstract : Aims: Mammary analogue secretory carcinoma (MASC) is a recently described salivary gland malignancy. This study evaluates the characteristics and long-term clinical behaviour of MASCs. Methods: Salivary gland malignancies at Royal Prince Alfred Hospital and Sydney Head and Neck Cancer Institute (1989–2014) were reviewed to identify MASCs. Histopathological evaluation, immunohistochemical and fluorescent in-situ hybridisation (FISH) studies were performed. Results: Ten cases of MASC were identified with age range 19–82 years (mean 41 years). The tumour size ranged from 14–50 mm (mean 22 mm) and commonly involved the parotid. MASCs predominantly showed a cystic pattern with thin, pale eosinophilic secretions and monotonous cells with vacuolated eosinophilic cytoplasm and a small nucleus with a small distinctive nucleolus. The tumours were positive with S100, MUC4, CK7, GCDFP-15 and negative for p63, CK5/6 and calponin. FISH showed ETV6 rearrangement in all tested cases with one case showing a novel rearrangement pattern. One case showed lymph node involvement. Local failure was seen in one patient. Conclusion: MASCs have relatively specific histopathological features and immunohistochemical profile that distinguish them from their mimics. FISH plays a confirmatory role. An indolent long-term clinical course was observed despite involvement of intraparotid lymph node and microscopically involved/close margins in 70% cases.